La restauración del claustro Santa Clara Real a través de oficios ancestrales (2021)
The cloister Santa Clara la Real located in the historic center of the city of Tunja, is a local reference of a comprehensive restoration of a property of heritage interest, carried out by the Escuela Taller de Boyacáfoundation, through the transmission of knowledge and trades as tools of significance, memory and appropriation of a place that was in a state of abandonment.